Synergistic Pt-WO3 Dual Active Sites to Boost Hydrogen Production from Ammonia Borane - Chen, Wenyao; Fu, Wenzhao; Qian, Gang; Zhang, Bingsen; Chen, De; Duan, Xuezhi; Zhou, Xinggui (iScience, 2020)
Development of synergistic heterogeneous catalysts with active sites working cooperatively has been a pursuit of chemists. Herein, we report for the first time the fabrication and manipulation of Pt-WO3 dual-active-sites to boost hydrogen generation from ammonia borane. A combination of DFT calculations, structural characterization, and kinetic (isotopic) analysis reveals that Pt and WO3 act as the active sites for ammonia borane and H2O activation, respectively. A trade-off between the promoting effect of WO3 and the negative effect of decreased Pt binding energy contributes to a volcano-shaped activity, and Pt/CNT-5W delivers a 4-fold increased activity of 710.1 molH2·molPt−1·min−1. Moreover, WO3 is suggested to simultaneously act as the sacrificial site that can divert B-containing by-products away from Pt sites against deactivation, yielding an increase from 24% to 68% of the initial activity after five cycles. The strategy demonstrated here could shed a new light on the design and manipulation of dual-active-site catalysts. [Display omitted] •Mechanism-guided design of Pt-WO3 dual active sites boosts H2 generation•A trade-off between WO3 loading and Pt B.E. yields a volcano-shaped activity•WO3 acts as the sacrificial site to divert by-products against deactivation•Multifunctional Pt-MO/C catalysts achieve enhanced activity and durability Inorganic Chemistry; Catalysis; Nanomaterials